Pelaksanaan Pemberian Hak Narapidana Mendapatkan Pembebasan Bersyarat (Studi Kasus di Rumah Tahanan Negara Kelas Iia Kerobokan) - I Dewa Gede Agung Ary Junaedi Saputra; Made Minggu Widiantara; Ni Made Sukaryati Karma (Jurnal Analogi Hukum, 2019)
Inmates who served the punishment in prison are often considered to have no rights of any kind. They are often treated in inhumane because they are considered to have committed a crime so that their actions must be in the prison. The rules regarding correctional system in force at the moment is Act No. 12 Year 1995 about a Correctional one of the conditions governing the rights of an Inmate that where there is a requirement of the Ordinance as well as in the implementation of those rights.Based on the foregoing formulated problems: 1) how is the implementation of the Rights of prison inmates get Parole in State Custody Homes class IIA Kerobokan?. 2) what are the obstacles that arise in the implementation of the grant of the rights of Convicts get Parole in State Custody Homes IIA Kerobokan?. Type of this research is the empirical research by reviewing the provisions of normative and use case study for non doktrinial. This research is predicated on research field, research libraries. This research was conducted at the home of State Prisoners Class IIA Kerobokan. Data research results, both primary data secondary data as well as processed and analyzed qualitatively. The implementation of the rights of prison inmates get parole is donebased on Regulation of the Minister of Justice and human rights Indonesian Republic No. D. 01. At 04.10 Year 2007. Barriers in the implementation of the grant of the rights of convicts get parole, Parole proposing Procedures are too complicated and take a long time to get a decision.